Nusantara Syariah Economy (Construction of Economic Cooperation between The Indonesian Muslim Community) - AM Hafidz Mashum; Marlina Marlina (IQTISHODUNA: Jurnal Ekonomi Islam, 2020)
This study seeks to answer two problem formulations, namely the construction of economic cooperation practices for the Indonesian Muslim community in agriculture, plantation, livestock, and forestry, and the feasibility of these economic cooperation practices in the Islamic banking industry. The results of this study conclude that the practice of economic cooperation between the Muslim community in the archipelago is constructed through six concepts, namely (1) adat; (2) social capital; (3) oral agreement; (4) profit sharing; (5) 'urf; (6) sharia compliance; and (7) muamalah fiqh contracts. When viewed from the sociological, juridical, and economic aspects, the practice of economic cooperation in the Indonesian Muslim community is a very potential captive market for Islamic banks. This research strengthens the Granoveterian embeddedness theory which states that economic behavior (in this case is the practice of economic cooperation between the Muslim community in the archipelago) is a social action that is socially structured and positioned. Research at the same time rejects Polanyian's embeddedness, which states that attachment only occurs in pre-industrial societies.